The effect of sleep quality on academic performance is mediated by Internet use time: DADOS study - Mireia Adelantado-Renau; Ana Diez-Fernandez; Maria Reyes Beltran-Valls; Alberto Soriano-Maldonado; Diego Moliner-Urdiales (Jornal de Pediatria, 2019)
Objective: The aims of the present study were to analyze the association of sleep patterns with academic and cognitive performance in adolescents, and to test the potential mediating effect of different activities of screen media usage on this association. Methods: A sample of 269 adolescents (140 boys) aged 14 years from the baseline data of the Deporte, ADOlescencia y Salud study completed questionnaires about sleep quality, cognitive performance, and leisure-time sedentary behaviors. Sleep duration was objectively computed using a wrist-worn GENEActiv accelerometer and academic performance was analyzed through school records. Results: Sleep quality (but not sleep duration) was associated with all the academic performance indicators (all p < 0.05). Analysis of covariance revealed higher grades among adolescents with better sleep quality (PSQI ≤ 5; all p < 0.05). These analyses showed no differences regarding cognitive performance. Internet use time was revealed as a mediator of the association between sleep quality and academic performance, being significant for all academic performance indicators (PM ranging from 15.5% to 16.0%). Conclusions: The association between sleep quality and academic performance in adolescents is mediated by time of Internet use. Overall, reducing Internet use in adolescents could be an achievable intervention for improving sleep quality, with potentially positive effects on academic performance. Resumo: Objetivo: Analisar a associação dos padrões de sono com o desempenho acadêmico e cognitivo em adolescentes e testar o efeito mediador potencial de diferentes atividades com uso de dispositivos (mídias) com tela nessa associação. Métodos: Uma amostra de 269 adolescentes (140 meninos) de 14 anos, da linha de base do estudo DADOS (Deporte, ADOlescencia y Salud) preencheu uma série de questionários sobre qualidade do sono, desempenho cognitivo e comportamentos sedentários no lazer. A duração do sono foi calculada objetivamente com um acelerômetro de pulso GENEActiv e o desempenho acadêmico foi analisado por meio de registros escolares. Resultados: A qualidade do sono (mas não a duração do sono) foi associada a todos os indicadores de desempenho acadêmico (todos os valores de p < 0,05). A análise de covariância revelou notas mais altas nos adolescentes com melhor qualidade de sono (PSQI ≤ 5; todos os valores de p < 0,05). Essas análises não mostraram diferenças em relação ao desempenho cognitivo. O tempo de uso da Internet revelou-se como um mediador da associação entre qualidade do sono e desempenho acadêmico, foi significativo para todos os indicadores de desempenho acadêmico (PM variou de 15,5% a 16,0%). Conclusões: A associação entre qualidade do sono e desempenho acadêmico em adolescentes é mediada pelo tempo de uso da internet. No geral, reduzir o tempo de uso da internet pelos adolescentes pode ser uma intervenção viável para melhorar a qualidade do sono, com efeitos potencialmente positivos no desempenho acadêmico. Keywords: School achievement, Cognition, Sleep patterns, Adolescence, Palavras-chave: Desempenho escolar, Cognição, Padrões de sono, Adolescência